The hammer of God - Clarke, Arthur C. (Arthur Charles), 1917-2008. (New York : Bantam Books, 1993)
In the year 2110, an amateur astronomer discovers a chunk of rock hurtling through space that could mean the end of Earth's civilization.
Out of Africa -- Rendezvous with Kali -- Stones from the sky -- The prophet -- Excalibur -- Europa station -- Astropol -- Anomaly -- Command decision -- Murphy's law.
Booklist starred.
Wilson's Fiction.
Wilson's Senior High School.
Adult
Keywords: Asteroids -- Fiction; Earth -- Fiction; End of the world (Astronomy) -- Fiction; Earth -- Fiction; End of the world -- Fiction; Science fiction